Upgrading and repairing build a PC with Scott Mueller - Mueller, Scott; Safari eBooks ([United States?] : Que, 2007)
"Scott Mueller's industry-leading classic Upgrading and Repairing PCs has taught millions of people how to diagnose, repair, and upgrade their PCs. Scott's books are used by thousands of hardware professionals, enthusiasts, and technicians worldwide and is found on the shelves of technicians at Intel, Dell, and Maximum PC. Now, Scott has created the ultimate companion to his highly successful series."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from title frames.
Electronic reproduction.
Keywords: Microcomputers -- Design and construction; Microcomputers -- Repairing; Electronic books